Membangun Keunggulan Bersaing Melalui Kualitas Produk, Persepsi Harga Dan Distribusi : (Sensus Pada Pelanggan PD.Tamansari Di Tasikmalaya) - Bella Putri Pangesti (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
: The purpose of this study was to determine and analyze the effect of Product Quality, Price Perception and Distribution on Competitive Advantage at PD Tamansari. The research method used in this study is causality research with a survey approach, while the types of data used in this study are quantitative and secondary data. The object of this research is the customer of PD Tamansari, with the sampling technique using the saturated sampling technique. The data analysis technique used is multiple regression analysis. The results of data analysis show that Product Quality, Price Perception and Distribution have a simultaneous and partial influence on competitive advantage at PD Tamansari.